Glycosphingolipid metabolic reprogramming drives neural differentiation. (27th December 2017) - Russo, Domenico; Della Ragione, Floriana; Rizzo, Riccardo; Sugiyama, Eiji; Scalabrì, Francesco; Hori, Kei; Capasso, Serena; Sticco, Lucia; Fioriniello, Salvatore; De Gregorio, Roberto; Granata, Ilaria; Guarracino, Mario R; et al.
Abstract: Neural development is accomplished by differentiation events leading to metabolic reprogramming. Glycosphingolipid metabolism is reprogrammed during neural development with a switch from globo‐ to ganglio‐series glycosphingolipid production. Failure to execute this glycosphingolipid switch leads to neurodevelopmental disorders in humans, indicating that glycosphingolipids are key players in this process. Nevertheless, both the molecular mechanisms that control the glycosphingolipid switch and its function in neurodevelopment are poorly understood. Here, we describe a self‐contained circuit that controls glycosphingolipid reprogramming and neural differentiation. We find that globo‐series glycosphingolipids repress the epigenetic regulator of neuronal gene expression AUTS2. AUTS2 in turn binds and activates the promoter of the first and rate‐limiting ganglioside‐producing enzyme GM3 synthase, thus fostering the synthesis of gangliosides. By this mechanism, the globo–AUTS2 axis controls glycosphingolipid reprogramming and neural gene expression during neural differentiation, which involves this circuit in neurodevelopment and its defects in neuropathology. Synopsis: Schematic representation of glycosphingolipid reprogramming circuit in neural differentiation. Globo‐series glycosphingolipids inhibit the production of ganglio‐series glycosphingolipids. AUTS2 expression is repressed by globo‐series glycosphingolipids. AUTS2 activates the promoter of the first and rate limiting enzyme involved in ganglio‐series glycosphingolipids production i.e., GM3 synthase by inducing histone acetylation. The globo‐AUTS2 axis regulates the expression of neuronal genes during neural differentiation. The decrease of globo‐series glycosphingolipids is required for AUTS2 induction and for stem cell differentiation to neural cells. Abstract : The switch from globo‐ to ganglio‐series glycophospholipids during neurodevelopment involves a self‐contained regulatory circuit controlling expression of both neuronal and ganglioside‐producing genes.